2015
DOI: 10.1002/pts.2139
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Transport Packaging and Repackaging into Modified Atmosphere on Shelf Life and Quality of Thawed Atlantic Cod Loins

Abstract: Boxes of expanded polystyrene (EPS, with or without ice added), corrugated cardboard (CC, with or without ice added) and polypropylene (PP, gel-ice inside the lid) were used in a case study, for transport of cod loins. Shelf life and quality were analysed after repackaging into modified atmosphere by use of culture dependent microbial methods, analysis of bacterial 16S rRNA sequences, sensory descriptive analysis and analysis of volatile components. The CC boxes showed faster temperature reduction compared to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 45 publications
1
9
0
Order By: Relevance
“…3; Table 3; Magnússon & Martinsdóttir, 1995;Roiha et al, 2017). However, a dominating microbiota, including Psychrobacter spp., as observed for batch B, was also previously reported (Hansen et al, 2015). The measured concentrations of Pseudomonas spp.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…3; Table 3; Magnússon & Martinsdóttir, 1995;Roiha et al, 2017). However, a dominating microbiota, including Psychrobacter spp., as observed for batch B, was also previously reported (Hansen et al, 2015). The measured concentrations of Pseudomonas spp.…”
Section: Discussionsupporting
confidence: 88%
“…Frozen storage for less than one months extended shelf-life of chilled refreshed cod marginally whereas sensory shelf-life was extended 3-4 days in ice following frozen storage periods up to twelve months (Magnússon & Martinsdóttir, 1995;Vyncke, 1983). After frozen storage during one to 12 months at -20 °C to -28 °C, several studies with cod from Belgium, Iceland and Norway found sensory shelf-life of 7 -15 days in ice for refreshed cod in air (Hansen et al, 2015;Martinsdottir & Magnusson, 2001;Roiha et al, 2017;Vyncke, 1983). Fresh cod from CBA in Greenland had sensory shelf-life of 15 days in air (Sørensen et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To extend shelf life, the processing and storage conditions should be optimized to prevent the growth of spoilage organisms present in fish. A common packaging method of gutted cod and cod fillets is aerobic storage in expanded polystyrene (EPS) boxes supplemented with ice to ensure a low chilling temperature [16]. Single packaged cod fillets and fillet products are also sold vacuum packaged or modified atmosphere packaged (MAP).…”
Section: Introductionmentioning
confidence: 99%
“…Some food packaging also include high levels of O 2 , which has shown to reduce the formation of TMAO to TMA in fish [23,24,[26][27][28]. However, the bacteriota under high O 2 storage has only been described in a few studies [16,23,24]. Studies also show that a mixture of bacteria presented during storage with a dominance of Photobacterium and Psychrobacter, followed by Moritella, Carnobacterium, Shewanella, and Vibrio as potential spoilage bacteria [29], and Carnobacterium spp.…”
Section: Introductionmentioning
confidence: 99%